Identification of a potential homeodomain-like gene governing leaf size and venation architecture in birch - Xiuyan Bian; Xiuyan Bian; Chen Chen; Chen Chen; Yang Wang; Yang Wang; Chang Qu; Chang Qu; Jing Jiang; Yao Sun; Guifeng Liu (Frontiers in Plant Science)
Leaf vein, an essential part of leaf architecture, plays significant roles in shaping the proper leaf size. To date, the molecular mechanisms governing leaf development including leaf venation patterning remains poorly understood in birch. Here, we performed the genome-wide identification of homeodomain-like (HD-like) superfamily genes using phylogenetic analysis and revealed the functional role of a potential HD-like gene in leaf growth and development using transgenic technology and transcriptomic sequencing. A total of 267 HD-like genes were identified based on Arabidopsis HD-containing transcription factors, which were members of KNOTTED1-like homeobox (KNOX) family, BELL1-like homeobox (BLH) family, Zinc finger-HD (ZHD) family, HD-leucine zipper (HD-Zip) family, Golden2, ARR-B, Psr1 (GARP) family, WUSCHEL-related homeobox (WOX) family, and Myeloblastosis (MYB) and MYB-like family. Further, 41 HD-like genes showing co-expression with marker genes related to leaf vascular tissues exhibited differential expression during primary vein development. Among them, a potential HD-like gene (BpPHD4) of GARP family served as a negative factor in governing leaf size and venation patterning. Compared to non-transgenic plants, BpPHD4 repression transgenic plants showed increased leaf length, leaf width, leaf area, leaf thickness, spongy tissue thickness, stomata number, epidermal cell size, primary vein length, the distance between the secondary veins, and primary vein diameter, which was opposite to those of BpPHD4 overexpression transgenic plants. Meanwhile, reduced expression levels of BpPHD4 could remarkably promote phloem tissue development. Transcriptome analysis of BpPHD4 overexpression transgenic plants showed two candidate genes (Bpev01.c0518.g0018 and Bpev01.c2797.g0002) probably regulated by BpPHD4. To conclude, our findings contribute to a better understanding of HD-like superfamily genes and unravel the role of a potential HD-like gene in genetically controlling leaf size and venation patterning in birch, which provides clues to genetic improvement of woody plants with diverse geometric and topological properties of leaf vascular network.